2014
DOI: 10.1007/s00380-014-0557-9
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of fibroblast growth factor 21 on atherosclerosis via amelioration of endoplasmic reticulum stress-mediated apoptosis in apoE−/− mice

Abstract: Fibroblast growth factor 21 (FGF-21) is an endocrine factor that can be secreted into circulation by the liver. FGF-21 takes part in metabolic actions and is thought to be a promising candidate for the treatment of diabetes. However, the role of FGF-21 in atherosclerosis is unknown. In this study, apoE(-/-) mice were fed an atherogenic diet for 4 weeks with and without subcutaneous injections of FGF-21. ApoE(-/-) mice fed an atherogenic diet showed hyperlipidemia, a large plaque area in aortas and increased ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 44 publications
4
44
1
Order By: Relevance
“…Moreover, in chronic MI (2 weeks) C57BL6 and adiponectin-KO mice models it was demonstrated that FGF21 protein derived from skeletal muscles protected the heart from apoptosis through adiponectin signaling (Joki et al 2015). In addition, FGF21 100 mg/kg per day s.c. injections for 4 weeks could protect the abdominal aorta from arteriosclerotic lesions through lipid regulation and ER stress induced vascular cell apoptosis in the ApoE-KO model (Wu et al 2014).…”
Section: Effects Of Fgf21 On Myocyte Apoptosis and Myocardial Infarctionmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, in chronic MI (2 weeks) C57BL6 and adiponectin-KO mice models it was demonstrated that FGF21 protein derived from skeletal muscles protected the heart from apoptosis through adiponectin signaling (Joki et al 2015). In addition, FGF21 100 mg/kg per day s.c. injections for 4 weeks could protect the abdominal aorta from arteriosclerotic lesions through lipid regulation and ER stress induced vascular cell apoptosis in the ApoE-KO model (Wu et al 2014).…”
Section: Effects Of Fgf21 On Myocyte Apoptosis and Myocardial Infarctionmentioning
confidence: 96%
“…A previous study demonstrated that cardiomyocytes secrete FGF21 into the media culture in basal conditions at a rate of w0.05 ng/ml per 24 h (Planavila et al 2013). In the heart, FGF21 ligands act via the FGFR1c (Suzuki et al 2008, Liu et al 2013, Planavila et al 2013, Wu et al 2014, and FGFR3 (Suzuki et al 2008, Liu et al 2013, utilizing b-Klotho as a co-receptor (Suzuki et al 2008, Liu et al 2013, Planavila et al 2013. Endogenous and exogenous FGF21 plays an anti-apoptotic role in both in vitro and in vivo models, partially through the adiponectin signaling cascade (Joki et al 2015).…”
Section: Effects Of Fgf21 On the Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that FGF21 was increased in the serum of human subjects with CAD and carotid artery plaques, and increased FGF21 levels were associated with adverse lipid profiles in CAD subjects (Lin et al 2010, Chow et al 2013. A recent study has shown that the serum FGF21 level was also increased in atherosclerosis-prone apolipoprotein E knockout (Apoe K/K ) mice fed an atherogenic diet (Wu et al 2014). FGF21 administration improved atherogenic diet-induced dyslipidemia and vascular atherosclerotic lesions in Apoe K/K mice, probably by mitigating ER stress, a contributing factor in the pathogenesis of atherosclerosis (Wu et al 2014).…”
Section: Fgf21 and Cardiovascular Diseasementioning
confidence: 97%
“…Macrophages are particularly vulnerable to lipidinduced toxicity; differentiation and recruitment of m a c r o p h a g e s t o p l a q u e s a c c e l e r a t e t h e development of atherosclerosis (Hotamisligil et al, 2008;Wu et al, 2015;Ren et al, 2017). Erbay and colleagues reported that mitigation of ERS with a chemical lipid chaperone (aP2) results in significant protection against dying lipotoxic macrophages and prevents atherosclerosis, while these effects are reversed in the aP2 knockout mouse.…”
Section: Fundamental Mechanisms P a T H O L O G I C A L E X A M I N Amentioning
confidence: 99%